Percepción de los docentes sobre sus alumnos migrantes en las escuelas primarias de la ciudad de Rosario, Argentina - Segura, María Laura (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
International migration towards Argentina have remained constant since the first national population census in 1869. Actually, Argentina is the chosen destination by migrants because of its geographical location and because of the migrant´s law that guarantees migrants rights and equal treatment, this point guarantees work possibilities and access to educations and health care. This work begins from study of contemporary migration with the propose of analyzing how educational speech tests the migrant students pupils performance in public and private primary schools in the city of Rosario. Migrants are in a visible place in the Argentina society, and teachers evidence what society built around migrants. This article is part of a wider investigation (2009-2012) in which we seek to investigate the inclusive actions from an intercultural approach and to indentify possible discrimination actions at schools and to note the processes of identity construction in migrant students. The focus target has been done in eight primary schools localized in different places of the city. Three techniques of data collection were used: interview, survey and observation from a qualitative and quantitative approach, prioritizing the qualitative. We have done a triangulation of all the information with the propose of reaching accuracy conclusions. In this opportunity we share the analysis about acts of discrimination in the primary schools.